The Economic Analysis for Construction in Ibn Khalduon s’ Muqaddimah - فرحان اسيا كاظم; مطلك هيثم حميد (Journal of Economics and Administrative Sciences, 2018)
The specialist researcher fined the relations between economic ideas with economic facts in his theory which called humanity building it is appeared clearly ( in Ibn Khalduons’ Muqaddimah) in a clothe of economic social phenomenon’s as a systematical analysis in all fifty chapters of al Muqaddimah ,therefore this paper deal with Ibn Khalduon economic thoughts as important says which describe the society building in its economic subjective and examine the relationship between The dissert and the city within economic says which are cover the social analysis ,and determinate the analysis objects which clearly in this dualism model ,between the state and economic base(Al mash ) ,so that Ibn Khalduon see the dramatic economic changes from the dessert to the city .Ibn Khalduon now how the civilization growth and decline by the economic factor which consider by Ibn Khalduon the first and greatest accomplish to classify the tow environments belongs to the ways to the human get there living from using the nature (means of production ) which leads to the production collections ,clearly growth within times. it is so much relatively to the conditions which role the tow economical model in society at fourteen century in morocco kingdoms .this paper leads us to describe and analyze the most important factors to decline the civilization of Morocco at that period by the economic factor which Ibn Khalduon thought it by the consumption civilization model because of destroying all capitalization in the two environments and didn’t moving to the capitalism system , therefore Ibn Khalduon ideas pattern to historical economical development of societies ,as a scientific method